STUDYING THE GREAT RUSSIAN REVOLUTION - A. V. Torkunov (Vestnik MGIMO-Universiteta)
The article revises an established view of Russian Revolution as two separate events - February Revolution and October Revolution. The author supports the concept of the «Great Russian Revolution», which unites these two events in a single process of revolutionary development. The author draws attention to the following advantages of the concept under consideration. First, it conceptualizes the revolution as a process contingent of a local and global historical context. In this sense, the revolution is presented as the transition of society to the modern stage of development, meaning the transition to modernity. Second, revolutionary events in Russia are considered from the point of view of the evolution of the spatial and socioeconomic distribution and rearrangement of key social groups: peasantry, elites, national and ethnic minorities. Third, it takes into account the personal factor in the revolutionary events, the influence of individual personalities on escalation or the reduction of socio-political tensions. Fourth, it draws attention to the fact that revolutions imply the use of various forms of political violence. Each revolution is characterized by a unique correlation of forms and intensity of political violence. Finally, it gives a normative assessment of the Revolution, encouraging a national discussion on the results and consequences of this great event.